PENETAPAN FLAVONOID TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DARI DAUN JAMBU AIR (Syzygium aqueum), DAUN JAMBU BOL (Syzygium malaccense) DAN DAUN JAMBLANG (Syzygium cumini) - Devie Maulani Zaen; Meiliza Ekayanti (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
The genus Syzygium family myrtaceae is one of the largest genus in Indonesia, of which species derived from guavas are water roseapple (Syzygium aqueum), red-jambo (Syzygium malaccense), and java plum (Syzygium cumini) which have natural antioxidant activity. This study aims to determine the total flavonoid content and antioxidant activity of species of the guava genus. The extraction method used in this research is cold extraction in the form of maceration with the choice of solvent ethanol 96%. The total flavonoid content test was carried out using the colorimetric method while the antioxidant power test used the DPPH (2,2-diphenyl-1-picridhydrazil) method. The results of total flavonoid levels in water roseapple is 156.897 ± 76.929 mgQE/g, red-jambo is 227.241± 107.882 mgQE/g and java plum is 239.425± 121.562 mgQE/g and the IC50 value for water roseapple is 5.416 ± 2,588 µg/mL, red-jambo is 3.297± 2.595 µg/mL and java plum is 2.416± 1.543 µg/mL. it can be concluded that jamblang leaf extract on total flavonoid levels and antioxidant test data obtained the highest antioxidant activity.